SusHi-Wat: Output of Beas-Sutlej basins systems model - Momblanch Benavent, Andrea; Holman, Ian P.; Papadimitriou, Lamprini; Jain, Sanjay K.; Kulkarni, Anil; Ojha, Chandra S. P.; Adeloye, Adebayo J. (Cranfield University, 2018)
This work has been developed under the project 'Sustaining Himalayan Water Resources in a Changing Climate' (SusHi-Wat), which aims at improving understanding of how water is stored in, and moves through, a Himalayan river system in northern India (the inter-linked Beas and Sutlej catchments) and develop and test a robust model of the whole system that can be used to inform current and future decision making to support the sustainable development and management of the region's water resources.The dataset contains the monthly time series of selected output of a water resource systems model built with the Water Evaluation And Planning (WEAP) software for the Beas and Sutlej basins, under different climate and socio-economic scenarios. It was used to derive the results presented in the paper "Untangling the water-food-energy-environment nexus for global change adaptation in a complex Himalayan water resource system", https://doi.org/10.1016/j.scitotenv.2018.11.045.Detailed description of the files:'0.Runoff summary.xlsx' - Monthly time series of the total runoff generated upstream Pong and Bhakra reservoirs for the baseline scenario and two climate change scenarios. The column headings correspond to different sub-basins and elevation bands as described in the corresponding paper.'1.WEAP results_Baseline.xlsx'; '1.WEAP results_CC3&SSP1.xlsx'; '2.WEAP results_CC3&SSP2.xlsx'; '3.WEAP results_CC3&SSP5.xlsx'; '4.WEAP results_CC7&SSP1.xlsx'; '5.WEAP results_CC7&SSP2.xlsx'; '6.WEAP results_CC7&SSP5.xlsx' - Monthly time series of several WEAP outputs under different climate and socio-economic change scenarios, i.e. urban demand supply coverage, irrigation demand supply coverage, hydropower energy production, water stored in reservoirs, river flows downstream Pandoh dam, glacier depth, total runoff, snow melt runoff, ice melt runoff, actual evapotranspiration. The column headings correspond to water demands, management infrastructures and sub-basins and elevation bands as described in the corresponding paper.
Keywords: WEAP'; 'drinking water demand coverage'; 'irrigation demand coverage'; 'hydropower generation'; 'environmental flow'; 'reservoir storage'; 'water yield'; 'snow melt'; 'glacier depth'; 'glacier melt'; 'actual evapotranspiration'; 'Hydrology'; 'Natural Resource Management'